Langkah Penyadaran Brand Usaha Kecil dan Menengah (Ukm) - Noor Udin (Humaniora, 2011)
Brand is an abstract term for actors in small and medium enterprises (SME). Moreover, it is hard to attach the term into understanding how they need branding. Understanding brand design is one step to synchronize the mind set of SME actors to map the business range, product understanding, and also their target market and other things related to their business. A good identity for an SME brand will create brand core value collaborated by complete understanding about entity aspects that having special ecosystem and unique. If thinking about long-term, SME actors will get many advantages from branding activity. Therefore, selling-based and branding activities are better moving together and strengthen each other.